Application of Lateral Wedge in Knee Osteoarthritis for Improving Pain and Quality of Life - Salam, Abdul; Awan, Muhammad Waqar; Mahmood, Tahir; Rukh, Muhammad Shah; Seffat, Nimra (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine the effectiveness of lateral wedge with and without conventional physiotherapy in relieving knee pain and quality of life in patients of knee Osteoarthritis. METHODOLOGY: This Randomized controlled study was conducted in Madina Clinics, Faisalabad. By using simple random technique 40 patients in range 40-60 years of age with clinically and radiologically diagnosed cases of grade II and III were studied, from February to August 2016. Subjects were divided in two groups with 20 subjects in each group. KOOS knee survey was used for the assessment of Quality of life. RESULTS: Mean total pain score on baseline of experimental group was 79.95±2.5 while the score amongst the control group was 79.95±7.69, after application of lateral wedges along with other treatments, score after 2nd week was 84.65 ± 2.94 while in control group was 80.25±2.9.97. After 4th week the symptoms score in experimental group was 83.00 ± 0.00 while control group was 88.95 ± 2.96. After the 6th week score was 91.5±14.5 of experimental and 81.8±9.5 of control group.These results of insole Wedges is also correlated with a lateral shift in the location of the COP in stance phase. Increase in the knee joint varus moment with insole Wedges suggests that the indication and limitations of laterally wedged insoles in general should be analysed in detail. CONCLUSION: This study concluded that the lateral wedges were significant in reduction of pain and symptoms as well as improve the quality of life.